Gnatoplasti Bilateral dengan Bantuan Cangkok Tulang pada Gnatoskisis: Laporan Kasus - Annisa basyira; Irwansyah Manurung (Lembaga Penelitian Universitas YARSI, 2026)
Introduction: Gnatoschizis (alveolar cleft), is a developmental defect of the maxillary alveolar bone, occurring in up to 75% of patients with cleft lip and palate. This condition may impair mastication and cause persistent oronasal fistulas if it is left untreated. Gnatoplasty with bone grafting is a reliable procedure to restore alveolar continuity and oral function. This report describes the management of bilateral gnatoschizis with bilateral gnatoplasty and bone graft reconstruction. Case Report: A 25-year-old female presented with nasal fluid leakage during meals. Two small openings were foung in the upper labial mucosa, forming oronasal communications. OPG and 3D CT scan confirmed anterior maxillary defects directly communicating with the nasal cavity. The patient treated by bilateral gnatoplasty under general anesthesia. Closure of nasal and oral mucosa were performed to seal the fistulas. Bone grafting followed without membrane coverage using AmGraft® (freeze-dried dentin matrix, allograft) and Bonefill Ortho® (bovine hydroxyapatite, xenograft). Postoperative CBCT demonstrated well-positioned grafts completely filling the defects and patient reported no nasal leakage and regained normal mastication. Discussion: This case highlights the effectiveness of gnatoplasty with bone grafting performed without membranes. This approach simplifies the procedure while still achieving both anatomical repair and functional rehabilitation. Conclusion: Bilateral gnatoplasty with bone graft reconstruction is effective for closing oronasal communication and restoring oral function, without using membranes, making this approach practical for patients with residual cleft defects.